Gross and ultrastructural examinations of equine infundibular cement and infundibular necrosis (caries) in horses - Kilic, S; Dixon, PM; Kempson, SA (Tubitak Scientific & Technological Research Council Turkey, 1997)
This study utilised 10 upper premolar 4 (PM4) and 11 molar 1 (M1) that were fractured or sectioned with a lathe or diamond saw. Most specimens were acid etched or decalcified and examined using light and scanning electron microscopes. Infundibular cement contained vascullar channels that extensively branched and tapered to the periphery of infundibular cement and were terminated prior to reaching the amelodentinal junction. These vascular characteristics seemed to prevent cemental necrosis to spread all over the infundibular cement. Some infundibular cements contained two types of hypoplasia in which the first one was small and was adjacent to the amelodentinal junction. The second type was diffuse and located in the middle of infundibular cement. This type hypoplasia may predispose infundibular cement to necrosis if it had a direct relationship with oral environment.
Keywords: horse; infundibulum; cement; hypoplasia; caries